2012
DOI: 10.1111/aogs.12042
|View full text |Cite
|
Sign up to set email alerts
|

Sharing experiences to improve bereavement support and clinical care after stillbirth: report of the 7th annual meeting of the international stillbirth alliance

Abstract: Stillbirth remains a global health challenge which is greatly affected by social and economic inequality, particularly the availability and quality of maternity care. The International Stillbirth Alliance (ISA) exists to raise awareness of stillbirth and to promote global collaboration in the prevention of stillbirth and provision of appropriate care for parents whose baby is stillborn. The focus of this ISA conference was to share experiences to improve bereavement support and clinical care. These issues, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
(70 reference statements)
0
26
0
1
Order By: Relevance
“…All patients, including infants who may have been exposed to HIV or other infectious diseases, need medical care that protects both them and their providers. Families with pregnancy or infant loss may also require additional support from the health system; this may include additional training of staff, more resources for pathology laboratories and audit systems, development of networks of peer support for families, and additional monitoring and counselling in subsequent pregnancies [12]. While cultural contexts vary, these basic principles should guide the provision of competent, supportive and dignified care for all patients [13].…”
Section: Defining Respectful and Dignified Care Of Newbornsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients, including infants who may have been exposed to HIV or other infectious diseases, need medical care that protects both them and their providers. Families with pregnancy or infant loss may also require additional support from the health system; this may include additional training of staff, more resources for pathology laboratories and audit systems, development of networks of peer support for families, and additional monitoring and counselling in subsequent pregnancies [12]. While cultural contexts vary, these basic principles should guide the provision of competent, supportive and dignified care for all patients [13].…”
Section: Defining Respectful and Dignified Care Of Newbornsmentioning
confidence: 99%
“…blood draws, injections) [25, 26]Poor rapport between patients and providersWomen blamed for poor neonatal outcomes, small infant, female newborn [2]Unnecessary separation of mother/parent/caregiver and newborn [31]Non-consented treatment of newborn [31]Lack of breastfeeding, thermal care or other postpartum support [15]Health system conditions and constraintsNot enough providers for mother and newborn [2]Providers with no/limited skills for newborn care [19, 32]Unavailable or insufficient equipment for newborn care [2]Room cold or dirty (e.g. exposure to bacteria) [33]Newborn left alone or unattended [1]Added category: Legal accountabilityNo birth/death registration [35]Poor governance of health system/no legal recourse for malpractice [19]Added category: Bereavement and posthumous careNo/inappropriate bereavement options offered [12]No options for autopsies/verbal autopsies [18]Deleted category: Sexual abuse No evidence for newborns …”
Section: Building On the Framework To Include Newbornsmentioning
confidence: 99%
“…Parents may regret their decision about autopsy as a result of poor communication or inadequate information [143]. A study found that 52% of bereaved parents reported a poor understanding of events surrounding the stillbirth and 71% were dissatisfied with information they were given [144]. Twice as many parents who declined an autopsy later regretted their decision compared to those who agreed to an autopsy (34.4% versus 17.4%) [134].…”
Section: Investigation Of Stillbirthmentioning
confidence: 99%
“…However, there is limited understanding about how the interactions between health care providers and parents impact on parent's perception of care and the decision making process about investigation into the cause of death [144].…”
Section: Investigation Of Stillbirthmentioning
confidence: 99%
See 1 more Smart Citation